1999
DOI: 10.1002/(sici)1098-2272(1999)16:1<95::aid-gepi8>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Major genetic effects on airway‐parenchymal dysanapsis of the lung: The Humboldt family study

Abstract: We examined familial resemblance and performed segregation analysis for the maximal expiratory flow rate at 50% of vital capacity (Vmax50) and the ratio of Vmax50 to forced vital capacity (FVC), based on data from 309 nuclear families with 1,045 individuals in the town of Humboldt, Saskatchewan, in 1993. Vmax50 is considered as an index of airway function and Vmax50/FVC is considered as an index of airway-parenchymal dysanapsis. Both Vmax50 and Vmax50/FVC were preadjusted for host characteristics (age, height,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Although dysanapsis may be a characteristic of the healthy individual, Green and colleagues also hypothesized that it may represent a susceptibility state for the development of COPD (17). Through segregation analysis, Chen and colleagues recently demonstrated that measures suggestive of dysanaptic lung growth may be under major genetic control (19). Further research is required to determine whether genes within the linkage peaks for FEF 25-75% , FEF 25-75% /FVC, and FEV 1 /FVC are important for lung growth and development and/or early inflammatory effects of smoking on airflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Although dysanapsis may be a characteristic of the healthy individual, Green and colleagues also hypothesized that it may represent a susceptibility state for the development of COPD (17). Through segregation analysis, Chen and colleagues recently demonstrated that measures suggestive of dysanaptic lung growth may be under major genetic control (19). Further research is required to determine whether genes within the linkage peaks for FEF 25-75% , FEF 25-75% /FVC, and FEV 1 /FVC are important for lung growth and development and/or early inflammatory effects of smoking on airflow obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…22 23 Dysanaptic lung growth may predispose to the development of obstructive lung disease 24 25 and may also predict airway hyperresponsiveness. 26 Chen and colleagues 27 have recently investigated whether dysanaptic lung growth has a genetic component. 27 They investigated Vmax 50 /FVC using segregation analysis and suggested that dysanaptic growth of the lung airways to parenchyma is under major gene control.…”
Section: Discussionmentioning
confidence: 99%
“…Further effects are seen throughout childhood, with early respiratory infections, environmental tobacco smoke [3] and air pollution [4] all associated with reduced lung function growth. The genetic factors associated with lung function in childhood have been less extensively studied but are clearly important [5–7]. Twin studies give heritability estimates as high as 77% for monozygotic twins [8].…”
Section: Introductionmentioning
confidence: 99%